Chiari 1 Malformation Presenting as Central Sleep Apnea during Pregnancy: A Case Report, Treatment Considerations, and Review of the Literature - St. Louis, Erik K.; Jinnur, Praveen; McCarter, Stuart J.; Duwell, Ethan J.; Benarroch, Eduardo E.; Kantarci, Kejal; Pichelmann, Mark A.; Silber, Michael H.; Boeve, Bradley F.; Olson, Eric J.; Morgenthaler, Timothy I.; Somers, Virend K. (Frontiers in Neurology, 2014)
Purpose: Chiari malformation (CM) type 1 frequently causes obstructive or central sleep-disordered breathing (SDB) in both adults and children, although SDB is relatively rare as a presenting manifestation in the absence of other neurological symptoms. The definitive treatment of symptomatic CM is surgical decompression. We report a case that is, to our knowledge, a novel manifestation of central sleep apnea (CSA) due to CM type 1 with severe exacerbation and initial clinical presentation during pregnancy. Methods: Case report from tertiary care comprehensive sleep medicine center with literature review of sleep-disordered breathing manifestations associated with CM type 1. PubMed search was conducted between January 1982 and October 2013. Results: We report a 25-year-old woman with severe central sleep apnea initially presenting during her first pregnancy that eventually proved to be caused by CM type 1. The patient was successfully treated preoperatively by adaptive servoventilation (ASV), with effective resolution of sleep-disordered breathing following surgical decompression, and without recurrence in a subsequent pregnancy. Our literature review found that 58% of CM patients with SDB had OSA alone, 28% had CSA alone, 8 (10%) had mixed OSA/CSA, and 6 (8%) had hypoventilation. Of CM patients presenting with SDB, 50% had OSA, 42% had CSA, 8% had mixed OSA/CSA, and 10.4% had hypoventilation. We speculate that CSA may develop in CM patients in whom brainstem compression results in excessive central chemoreflex sensitivity with consequent hypocapnic CSA. Conclusions: CM type 1 may present with a diversity of SDB manifestations, and timely recognition and surgical referral are necessary to prevent further neurological deficits. ASV therapy can effectively manage CSA caused by CM type 1, which may initially present during pregnancy.